Characterization of GFP expression driven by powdery mildew promoters in a magnaporthe host / Nurul Aina Ismail and Marlina Mohd Mydin - Ismail, Nurul Aina; Mohd Mydin, Marlina (2012)
Powdery mildew is caused by the ascomycete fungus, Blumeria graminis f. sp. hordei (Bgh). Bgh is an obligate biotrophic pathogen which relies on its host for development and completion of its life cycle. The obligate nature of this fungus has hindered attempts to carry out biochemical and molecular biology analysis. Due to this, characterization of Bgh H4 genes which encodes for histone-4 protein involved in chromatin formation and DNA packaging was carried out in Magnaporthe oryzae, a non-obligate ascomycete fungus, pathogenic on rice. A GFP expression vector, under the control of Bgh H4 promoter was transformed in the wild-type M. oryzae strain. 3 independent replicates were obtained from different transformation attempts and were classified as P7.1, P7.15 and P7.16. The GFP expression was characterized at different time-points throughout M. oryzae life cycle on 4 different surfaces; onion epidermis, barley leaves, glass slides and cellulose membrane. Epifluorescence microscope was used to determine GFP expression based on its fluorescent intensity. These results were then compared to the experimental control, pMJK27.2, the primary vector construct which expressed GFP under the control of M oryzae MPG1 promoter. All P7 transformants exhibit low GFP expression compared to the control. Completion of infection cycle was obtained on onion epidermis and barley leaves whereas on glass and cellulose membrane, the growth of transformants halted following the formation of appresorium. Apart from that, malformed features such as long, branched and multiple germ tubes were also observed on glass and cellulose. Generally, a pattern of decreasing in fluorescent intensity was observed in different developmental structures as time progresses, with P7 transformants exhibited varying fluorescent intensities at each timepoints. The GFP expression level of P7 transformants at 0, 4, 8 and 16 hours post inoculation on barley leaves and cellulose membrane were also assessed by performing quantitative-PCR. Based on the analysis, the general trend of GFP expression on these surfaces does not appeared to fit the Bgh H4 expression profile gauged by microarray data analysis carried out in the past.